Italian Residential Buildings: Economic Assessments for Biomass Boilers Plants. (7th November 2013) - Carlini, Maurizio; Castellucci, Sonia; Cocchi, Silvia; Allegrini, Elena; Li, Ming
Abstract : Biomass is increasingly used for energy generation since it represents a useful alternative to fossil fuel in order to face the pollutions and the global warming problem. It can be exploited for heating purposes and for supplying domestic hot water. The most common applications encompass wood and pellet boilers. The economic aspect is becoming an important issue in order to achieve the ambitious targets set by the European Directives on Renewable Sources. Thus, the present paper deals with the economic feasibility of biomass boiler plants with specific regard to an existing residential building. An Italian case study is further investigated, focusing the attention on European and national regulations on energy efficiency and considering the recent public incentives and supporting measures. The main thermoclimatic parameters—that is, heating degree days (HDDs), building thermal insulation and thermal needs—are taken into account. Moreover, the following economic indicators are calculated: cumulative cash flow, discounted cumulative cash flow, payback period (PP), net present value (NPV), Internal rate of return (IRR), discounted payback period (DPP), and profit index (PI).